Morphological features and composition of noble metal minerals in disseminated and massive ores of the central part of the Oktyabrskoe deposit, Norilsk region - L. S. Canhimbue; N. D. Tolstykh; N. А. Krivolutskaya; I. V. Talovina (Известия высших учебных заведений: Геология и разведка, 2024)
Background. The composition of ores and noble metal minerals (NMM) in the Oktyabrskoe deposit of the Norilsk region varies significantly. An analysis of NMM occurrence forms and their associations may elucidate the conditions of their appearance in ores. Research into the morphology of these minerals is of fundamental importance for solving technological issues of their extraction from sulfide ores.Aim. To analyze the occurrence forms and associations of NMM to determine their formation conditions.Materials and methods. In total, 44 polished sections obtained from drill-core holes in the central part of the Oktyabrskoe deposit were examined. The composition and morphology of NNM samples were analyzed by scanning electron microscopy.Results. Forms of NMM in sulphide ores have been studied and the density of their aggregates has been determined. Different NMM paragenesis depending on the composition of sulphide ores was revealed. The hypothesis of the existence of an inverse relationship between the NMM crystallisation temperature and sulphur fugacity in the ore-forming system was confirmed.Conclusion. In the central part of the Oktyabrskoe deposit, the composition of NMM and their occurrence forms differ significantly depending of the type of sulfide ores and reflecting the genetic features of their mineralization. Differences in NMM paragenesis indicate a separate, independent evolution of each type of disseminated and massive ores under different conditions. This allows us to update the established model of ore formation in the Oktyabrskoe deposit.